Clinical and radiographic outcomes after pulpotomies using mineral trioxide aggregate mixed with distilled water or 2.25% sodium hypochlorite gel: a randomized controlled clinical trial - Karkoutly, Mawia; Abu Hasna, Amjad [UNESP]; Nam, Ok Hyung; Machado, Ricardo; Al Kurdi, Saleh; Bshara, Nada (Springer Nature, 2025)
ObjectivesSodium hypochlorite (NaOCl) gel is an effective additive for white mineral trioxide aggregate (WMTA) that enhances its chemical and physical characteristics and significantly reduces setting time while maintaining biocompatibility. The study sought to compare the outcomes of pulpotomies performed in primary teeth using WMTA mixed with 2.25% NaOCl gel or WMTA mixed with distilled water (DW).Materials and methodsIt was a randomized, triple-blinded, split-mouth, controlled clinical trial. Forty primary second molars from cooperative children aged 5–10 who required pulpotomy were randomly assigned to the control group—WMTA  + DW or experimental group—WMTA + NaOCl gel for clinical and radiographic assessments at 3, 6, and 12 months of follow-up. The clinical evaluation involved checking for spontaneous pain, pain on percussion, tooth mobility, abscesses, sinus tracts, and the exfoliation of the treated tooth. The periapical radiographic evaluation identified whether there was furcal radiolucency, internal or external root resorption, and widening of the periodontal ligament. Canal obliteration was not considered a failure.ResultsThe WMTA + NaOCl gel group showed a 90% and 95% clinical and radiographical success rate, respectively, at 3, 6, and 12 months of follow-up. In the control group, the clinical success rate was 90% after 3, 6, and 12 months, whereas the radiographical success rate was 100% at 3 months and decreased to 95% after 6 and to 85% after 12 months. No statistically significant difference was detected between the two groups (p > 0.05).ConclusionsThe present research validated WMTA + NaOCl gel as a potentially effective material for pulpotomy in primary molars.